2019
DOI: 10.1186/s40814-019-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of integrating vestibular rehabilitation and cognitive behaviour therapy for people with persistent dizziness

Abstract: Purpose To evaluate the feasibility of integrating vestibular rehabilitation and cognitive behaviour therapy (VR-CBT) for people with persistent dizziness in primary care. Design Prospective single-group pre- and post-test study. Participants Adults (aged 18–70) with acute onset of dizziness and symptoms lasting a minimum 3 months, recruited from Bergen municipality. Methods Participants attended eight weekly group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
2
13
0
1
Order By: Relevance
“…Skills and vestibular function were more preserved in p-PPPD, but the subjective symptom burden remained high and remarkable differences between p-and s-PPPD in terms of life quality as assessed by EQ5D-3L were lacking. However, overall quality of life was significantly reduced in both groups (VAS 58%) compared to healthy subject collectives, which is in line with earlier reports [43,44]. The discrepancy between the high subjective burden in PPPD and the objective vestibular function is underlined by the lack of a significant correlation between DHI, VAP, and QoL scores and objective neurophysiological parameters (e.g., in vHIT and caloric testing).…”
Section: Pppd Generally Prefer Red Female Gendersupporting
confidence: 90%
“…Skills and vestibular function were more preserved in p-PPPD, but the subjective symptom burden remained high and remarkable differences between p-and s-PPPD in terms of life quality as assessed by EQ5D-3L were lacking. However, overall quality of life was significantly reduced in both groups (VAS 58%) compared to healthy subject collectives, which is in line with earlier reports [43,44]. The discrepancy between the high subjective burden in PPPD and the objective vestibular function is underlined by the lack of a significant correlation between DHI, VAP, and QoL scores and objective neurophysiological parameters (e.g., in vHIT and caloric testing).…”
Section: Pppd Generally Prefer Red Female Gendersupporting
confidence: 90%
“…In addition, the study utilizes standardised testing procedures, evaluating both short-and long-term efficacy. Another strength is the initial feasibility study conducted, showing that test procedures and interventions were feasible and sage for the present population (27). To our knowledge, the current RCT study is the largest study to date, combining VR and CBT to treat persons with persistent dizziness.…”
Section: Discussionmentioning
confidence: 86%
“…The study is designed as a randomised controlled trial comparing two groups (BI-VR, and BI-VR with VR-CBT). To obtain a clinical important group difference in DHI of 11 points 38 based on drop-outs in the feasibility study (27), and in previous studies (18,20,57,58).…”
Section: Sample Size and Power Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, as none of the combined treatments included a focus on musculoskeletal complaints, there is a need to further develop the treatment combining VR and CBT, also targeting the musculoskeletal aspects, and afterward the effects of the programme must be tested in a RCT. A recent feasibility study integrating VR and CBT with an additional focus on musculoskeletal effects showed that such a treatment approach was feasible and safe [27]. Therefore, this treatment is now ready to be evaluated in a RCT.…”
Section: Introductionmentioning
confidence: 99%